2021
DOI: 10.1007/s12274-021-3894-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of celastrol to glomerular endothelium and podocytes for chronic kidney disease treatment

Abstract: The etiology of chronic kidney disease (CKD) is complex and diverse, which could be briefly categorized to glomerular- or tubular-originated. However, the final outcomes of CKD are mainly glomerular sclerosis, endothelial dysfunction and injury, and chronic inflammation. Thus, targeted delivery of drugs to the glomeruli in order to ameliorate glomerular endothelial damage may help alleviate CKD and help enrich our knowledge. The herb tripterygium wilfordii shows therapeutic effect on kidney disease, and celast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…The hemolysis ratio of CSL/SBE 7 -b-CD/HDBAC was calculated to be B0.5%, which was lower than the safety level of biomaterials (5%). 49 The above results confirmed that CSL/SBE 7 -b-CD/HDBAC possesses favorable blood compatibility which ensures its safety in blood.…”
Section: Hemolysis Of Csl/sbe7-b-cd/hdbacsupporting
confidence: 65%
“…The hemolysis ratio of CSL/SBE 7 -b-CD/HDBAC was calculated to be B0.5%, which was lower than the safety level of biomaterials (5%). 49 The above results confirmed that CSL/SBE 7 -b-CD/HDBAC possesses favorable blood compatibility which ensures its safety in blood.…”
Section: Hemolysis Of Csl/sbe7-b-cd/hdbacsupporting
confidence: 65%
“… 41 Celastrol has recently been proven to restrain cancers, obesity, and inflammation. 22 , 42 , 43 Recent research has demonstrated that celastrol can treat CKD, 44 obesity-associated nephropathy 45 and mesangioproliferative glomerulonephritis 46 by acting as an anti-inflammatory agent and inhibiting the production of cytokines. Celastrol has also been shown to be effective in regulating insulin resistance and autophagy in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, nanoparticles targeted to inflamed glomerular endothelium were loaded with a traditional Chinese root extract possessing anti-inflammatory effects, which reduced kidney disfunction and proteinuria in advanced IgA nephropathy. The anti-inflammatory properties were shown to be driven by increased eNOS expression and reduced VCAM-1 expression [14 ▪ ].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%